Pengaruh Model Project Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Ramadhani; Rais, Hidayati; Bahasa Indonesia, Bahasa Indonesia (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
The purpose of this study was to determine and describe the mathematical problem-solving ability before and after being taught using a project-based learning model. This type of research is quasi-experimental with posttest-only control design. This research was conducted at SMK N 10 Merangin with a population of 169 grade X students and simple random sampling to provide equal opportunities for each member of the population to be selected as a sample. The selected samples were 28 students of class X Visual Communication Design (DKV) and 28 students of Engineering and Motorcycle Business 1 (TBSM 1). The research instrument in the form of an essay test totaling 5 items that have been tested for validity, and significance, with a medium and easy difficulty index according to the indicators of mathematical problem-solving ability and reliability. Data analysis technique with normality test using Kolmogorov-Smirnov and Hartley test for homogeneity. Data analysis obtained the score of mathematical problem-solving skills of the experimental class 49.39 and the control class 43.54. The mastery level of mathematical problem-solving skills of the experimental class was 81%, and the control class was 71.5%. Because the data is normally distributed and the variance is not homogeneous, the hypothesis test was obtained, and dan dengan > atau 3,848 > 1,771. So, it can be concluded that the Mathematical Problem-Solving Ability taught with project-based learning is better than conventional learning with the expository method for class X students of SMKN 10 Merangin in the 2024/2025 academic year.